“Russian-Cost” as a “New” russian Method of Corporate Cost Accounting and Management - L. G. Cherednichenko; R. V. Gubarev; E. I. Dzyuba; Yu. V. Tyulenev; F. S. Fayzullin (Учёт. Анализ. Аудит)
Currently a number of Russian companies suffer the oppression of sectoral sanctions, and therefore the issue of ensuring economic security, especially of industrial enterprises, which play a key role in the national security of Russia, is of particular relevance. In the authors’ opinion, such security can be ensured by means of effective corporate cost accounting and management on the basis of reasonable local managerial ideology and modern information technologies. The article discusses the fundamental principles of the authors’ “Russian-cost” managerial ideology and the corporate cost accounting and management method carrying the same name. The ability of the enterprise to allocate expenses by the divisions participating in production is an indispensable condition of applying this method. The starting point of ideology is that no enterprise can have divisions without their own economically justified significance. As a result, within the enterprise, a closed circle of income and expenses is formed, which “pushes out” expenses and encourages divisions to increase income. Within this circle expenses can be “exchanged” for a salary and other incentives, resulting into the effect of “self-outsourcing”. In the long run, the company’s management has an opportunity to take effective managerial decisions based on the objective evaluation of each division’s “contribution” to financial results of the enterprise performance. “Russian-cost” is, first of all, an information and management shell, within which entrepreneurial plans and specified (for example, by the owner) parameters of the enterprise functioning can be implemented, i.e., it is a tool, ideology which inter alia can be used as a basis to build an automated management system.